High-intensity focused ultrasound combined with hysteroscopic insertion of levonorgestrel-releasing intrauterine system for intrinsic adenomyosis: a retrospective observational study - Yanjun Kang; Changmei Sang; Lei Zhao; Kun Ding; Shuping Zhao (International Journal of Hyperthermia)
Objective To retrospectively analyze the safety and efficacy of high-intensity focused ultrasound (HIFU) combined with hysteroscopic insertion of Levonorgestrel-Releasing Intrauterine System the treatment of intrinsic adenomyosis.Methods A total of 30 patients with intrinsic adenomyosis were enrolled. All patients initially underwent HIFU treatment, followed by hysteroscopic surgery to remove the remaining unabsorbed necrotic tissue and simultaneously insert the levonorgestrel-releasing intrauterine system (LNG-IUS) for long-term management of adenomyosis. The treatment results, adverse events, and 2-year follow-up data were analyzed statistically.Result All 30 patients successfully completed the treatment without serious complications, and achieved remarkable symptom improvement. The VAS score of dysmenorrhea and MSF score of menorrhagia both decreased significantly (p < 0.05). Uterine volume decreased significantly after treatment (p < 0.05). The proportion of patients with dysmenorrhea and menorrhagia who experienced significant symptom relief was 86.7% and 93.3%, and the clinical efficacy rates were 93.3% and 96.7% respectively, with no recurrent cases. LNG-IUS was inserted during hysteroscopic surgery in 30 patients. Up to the time of submission, no significant symptom recurrence and the LNG-IUS displacement rate is 3.3%.Conclusion Combination of HIFU and hysteroscopic insertion of Levonorgestrel-Releasing Intrauterine System is an effective and recommended therapeutic strategy for treating intrinsic adenomyosis.